An Informal Internet Survey on the Current State of Consciousness Science - Michel, Matthias; Fleming, Stephen M.; Lau, Hakwan; Lee, Alan L. F.; Martinez-Conde, Susana; Passingham, Richard E.; Peters, Megan A. K.; Rahnev, Dobromir; Sergent, Claire; Liu, Kayuet (Frontiers in Psychology, 2018)
The scientific study of consciousness emerged as an organized field of research only a few decades ago. As the solid empirical findings have greatly enhanced our understanding of consciousness, it is important to find out whether other factors, such as funding for consciousness research and status of consciousness scientists, provide a suitable environment for the field to grow and develop sustainably. We conducted an online survey from January to February in 2018 on people’s view regarding various aspects in the scientific study of consciousness as a field of research. 249 participants completed the survey, among which 80% were in academia, and around 40% were experts in consciousness research. Topics covered include the progress made by the field, funding for consciousness research, job opportunities for consciousness researchers, and the scientific rigor of the work done by researchers in the field. The majority of respondents (78%) indicated that scientific research in consciousness had been making progress. However, among those who knew about the situation (around 55% of all respondents), most (around 70-80%) perceived obtaining funding and getting a job in the field of consciousness research as more difficult than in other subfields of neuroscience. Overall, work done in consciousness research was perceived to be less rigorous than other neurosciences subfields (around 80% out of the 42% who knew about the situation), but this perceived lack of rigor was not related to the perceived difficulty in finding jobs and obtaining funding. Lastly, we found that, overall, the global workspace theory was perceived to be the most promising (around 28%), while most non-expert researchers (around 22% of non-experts) found the information integration theory (IIT) most promising. We believe the survey results provide an interesting picture of current opinions from scientists and researchers about the progresses made and the challenges faced by consciousness research as an independent field. They will inspire collective reflection on the future directions regarding funding and job opportunities for the field.